1989
DOI: 10.1177/07399863890111007
|View full text |Cite
|
Sign up to set email alerts
|

The Suinn Mathematics Anxiety Rating Scale (MARS-E) for Hispanic Elementary School Students

Abstract: The Suinn Mathematics Anxiety Rating Scale, Elementary Form (MARS-E) is described with a sample of 105 Hispanic students. These elementary school students were from six public schools. The test is composed of 26 items that measure anxiety in specific life activities. Results indicated that the MARS-E scores are correlated with scores on a mathematics test, the Stanford Achievement Test (SAT). Similarities in the average level of mathematics anxiety were found between Hispanics and the normative non-Hispanic gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…Previous studies with individuals from fourth grade to adulthood have found mathematics anxiety to be a multidimensional construct, involving anxiety related to evaluation and anxiety related to performance (e.g., Chiu & Henry, 1990;Hembree 1990;Ma, 1999;Suinn et al, 1988Suinn et al, , 1989. Worry and negative reactions have also been identified as components of mathematics anxiety specifically for students in late elementary through high school (Ho et al, 2000;Wigfield & Meece, 1988).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies with individuals from fourth grade to adulthood have found mathematics anxiety to be a multidimensional construct, involving anxiety related to evaluation and anxiety related to performance (e.g., Chiu & Henry, 1990;Hembree 1990;Ma, 1999;Suinn et al, 1988Suinn et al, , 1989. Worry and negative reactions have also been identified as components of mathematics anxiety specifically for students in late elementary through high school (Ho et al, 2000;Wigfield & Meece, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…When these findings are coupled with the well-documented relation between mathematics anxiety and mathematics performance, there is a considerable need to explore the role of mathematics anxiety in explaining this underachievement. In one of the few relevant studies, Suinn, Taylor, and Edwards (1989) found that fourth-through sixth-grade students identified as Hispanic (n = 105) did not differ from their White peers on levels of mathematics anxiety, suggesting that mathematics anxiety plays a limited role in explaining demographic risk for Hispanic children; Suinn and colleagues did not specify whether the Hispanic children in their study were language minority learners or native English speakers. Similarly, in a meta-analysis, Ma (1999) did not find differences in mathematics anxiety between white and minority samples, while noting the lack of studies in this area.…”
Section: The Nature Of Mathematics Anxietymentioning
confidence: 95%
“…Teachers’ math anxiety and math knowledge were assessed during the last 2 months of the school year. Math anxiety was assessed using the short Mathematics Anxiety Rating Scale (sMARS) ( 20 ), which is a 25-item version of the widely used 98-item MARS ( 21 ). Teachers responded to questions about how anxious different situations would make them feel (e.g., “reading a cash register receipt after you buy something,” “studying for a math test”).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, the language of mathematical discourse was identified as a possibly link to improved understanding and scaffolding of mathematics learning. When mathematical anxiety was correlated with scores on the Stanford Achievement Test (SAT), similarities were found between Hispanic and non-Hispanic students (Suinn 1989). Telese (1997) and Butty (2001) found a positive correlation between achievement and anxiety with a higher correlation in non-traditional, reform classrooms in schools with large Hispanic populations.…”
Section: Variables That Contribute To Hispanic Student Successmentioning
confidence: 99%